2023
DOI: 10.1371/journal.pone.0289382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with long COVID and mental health status among recovered COVID-19 patients in southern Thailand

Doan Hoang Phu,
Sarunya Maneerattanasak,
Shamarina Shohaimi
et al.

Abstract: Mental health disorders have become a growing public health concern among individuals recovering from COVID-19. Long COVID, a condition where symptoms persist for an extended period, can predict psychological problems among COVID-19 patients. This study aimed to investigate the prevalence of long COVID and mental health status among Thai adults who had recovered from COVID-19, identify the association between the mental health status and long COVID symptoms, and investigate the risk factors associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…In terms of disease conditions, our results highlighted associations between depression, anxiety, and stress with underlying diseases, such as non-communicable diseases, hypertension, diabetes, heart disease, and respiratory disease. This aligns with existing research emphasizing that underlying diseases are significant risk factors contributing to the severity of symptoms related to depression, anxiety, and stress [36][37][38], underscoring the need for heightened mental health awareness, particularly among those with underlying health issues.…”
Section: Discussionsupporting
confidence: 75%
“…In terms of disease conditions, our results highlighted associations between depression, anxiety, and stress with underlying diseases, such as non-communicable diseases, hypertension, diabetes, heart disease, and respiratory disease. This aligns with existing research emphasizing that underlying diseases are significant risk factors contributing to the severity of symptoms related to depression, anxiety, and stress [36][37][38], underscoring the need for heightened mental health awareness, particularly among those with underlying health issues.…”
Section: Discussionsupporting
confidence: 75%
“… 19 Similarly, in Thailand, Phu et al reported that individuals experiencing Long COVID symptoms were at a substantially higher risk of depression (OR 4.00) and anxiety (OR 6.93) in a study involving 939 hospitalised patients between January 2021 and May 2022. 20 The variation in increased risk may be attributable to differences in participant characteristics; for example, their cohorts were hospital based, whereas our study used general EHR data. Additionally, our approach involved survival analysis to account for time-to-event data and censoring, in contrast to these studies that employed logistic regression models for binary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors, on the other hand, must remain "self-confident for continuing life" and not be afraid of the possibility of reinfection. According to Phu et al [16], those who have previously had COVID-19 are at a higher risk of experiencing mental health problems such as worry, stress, and depression, potentially arising from the fear of reinfection, the sense of isolation, or the persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pumipak et al [15] conducted telephone interviews with individuals suffering from moderate to severe COVID-19 infections and receiving outpatient care in Bangkok, focusing on symptom experience and perceived health status. Similarly, Phu et al [16] studied Thai adults who had recovered from COVID-19, investigating associations between mental health issues and long-term COVID-19 symptoms among the participants. However, there is a dearth of information about the lived experience of COVID-19 patients from Thailand, especially having a combined study on the COVID-19 patient's pre-illness history, including pre-admission, hospitalization, and reintegration into their community.…”
Section: Introductionmentioning
confidence: 99%